2021
DOI: 10.1155/2021/9394563
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA SNHG15 Promotes Ovarian Cancer Progression through Regulated CDK6 via Sponging miR-370-3p

Abstract: Ovarian cancer is a kind of cancer from the female genital tract; the molecular mechanism still needs to be explored. lncRNA plays a vital role in tumorigenesis and development. Our aim was to identify oncogenic lncRNAs in ovarian cancer and explore the potential molecular mechanism. SNHG15 was initially identified by using GEO datasets (GSE135886 and GSE119054) and validated by tumor tissues and the cell line, identifying that SNHG15 was upregulated in ovarian cancer. Besides, high SNHG15 indicated poor progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…A previous study has revealed that miR-204 suppresses nonsmall cell lung cancer (NSCLC) progression through downregulating the CDK6 level [ 28 ]. Similarly, a recent study has indicated that miR-370-3p restrains the progression of ovarian cancer by reducing CDK6 expression [ 29 ]. Moreover, miR-576 represses CDK6 expression to promote bladder cancer cell proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has revealed that miR-204 suppresses nonsmall cell lung cancer (NSCLC) progression through downregulating the CDK6 level [ 28 ]. Similarly, a recent study has indicated that miR-370-3p restrains the progression of ovarian cancer by reducing CDK6 expression [ 29 ]. Moreover, miR-576 represses CDK6 expression to promote bladder cancer cell proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with the result reported by Liu and Huang [ 10 ] that knocking down SNHG15 inhibited the proliferation of osteoclasts. What is more, SNHG15 has been reported to regulate the proliferation and metastatic of oral squamous cell carcinoma [ 25 ], ovarian cancer [ 26 ], and bladder cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, RAB17 is a direct target of miR-370-3p. Furthermore, miR-370-3p arrests the cell cycle and promotes apoptosis of ovarian cancer cell through inhibiting CDK6 (25). SLD5, a component of the GINS complex, is crucial for DNA replication (62).…”
Section: The Biological Role Of Mir-370 In Cancermentioning
confidence: 99%
“…In ovarian cancer, miR-370-3p restrains cell proliferation and promotes apoptosis by targeting CDK6 (25). Furthermore, miR-370-3p can suppress colony formation of ovarian cancer cells via targeting RAB17 (61).…”
Section: The Biological Role Of Mir-370 In Cancermentioning
confidence: 99%
See 1 more Smart Citation